PENGARUH BEBAN KERJA, KOMPENSASI DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PADA PT. BPR PIJER PODI KEKELENGEN CABANG SIMPANG SELAYANG - Pandiangan, Joy Roberto; Tinambunan, Anitha Paulina (KUKIMA : Kumpulan Karya Ilmiah Manajemen, 2024)
This study aims to determine and explain the effect of workload, compensation and organizational culture on employee performance at PT. BPR Pijer Podi Kekelengen Simpang Selayang Branch. Data were obtained directly from respondents (employees) at PT. BPR Pijer Podi Kekelengen Simpang Selayang Branch. The population of this study was 34 people and the number of samples through saturated sampling techniques or census was 34 people. The analysis techniques used in this study were validity and reliability tests, measurement model analysis (outer model), structural model eval_uation (inner model) and eval_uation of the goodness and suitability of the model. The results of the study indicate that there is a relationship between the independent variables, namely workload, compensation and organizational culture, and the dependent variable, namely employee performance at PT. BPR Pijer Podi Kekelengen Simpang Selayang Branch. From the results of the structural model eval_uation test (inner model) there is a significant influence of workload on employee performance with t statistic (2.174) calculation result greater than 1.96 (t table) and p-value (0.015 <0.05), there is a significant influence of compensation on employee performance with t statistic (2.193) calculation result greater than 1.96 (t table) and p-value (0.014 <0.05), there is a significant influence of organizational culture on employee performance with t statistic (2.296) calculation result greater than 1.96 (t table) and p-value (0.011 <0.05). From the results of the eval_uation of the goodness and suitability of the model, it can be concluded that the model estimate is 0.086 which means that the model has an acceptable fit. Empirical data can explain the influence between variables in the model. The results of the determinant coefficient test (R Square) are 0.726. This means that employee performance can be explained by workload, compensation and organizational culture by 76.2% while the remaining 23.8% can be explained by other factors not examined in this study.